Digital Picture Storybooks, Can Increase Students' Self-Efficacy and Interest in Learning? - Muhammad Nazimuddin Al Kamil; Rita Eka Izzaty; Nur Patmawati (Universitas Pendidikan Ganesha, 2023)
There are still many students who need help with self-efficacy. This problem has an impact on the low interest in learning. One way to overcome these problems is to use appropriate learning media. This study aims to produce digital picture storybooks reviewed from the feasibility aspect based on the results of validation by experts and to know the practicality and effectiveness of digital picture storybooks in increasing self-efficacy and learning interest in fourth-grade elementary school students. This research is research and development with the Borg & Gall model. Data collection was carried out through interviews, scales, and questionnaires. Data analysis used the N Gain test, Independent Sample t-Test, Paired Sample t Test, and the MANOVA test. The results showed that digital picture storybooks were feasible to use based on the results of the validation of material experts and the results of validation of media experts and practical use based on the results of the teacher's response questionnaire and the results of student responses. The results of the N Gain test showed an increase in self-efficacy and student learning interest in the experimental group, which was higher than the control class. It was concluded that digital picture storybooks effectively increased the self-efficacy and learning interest of fourth-grade elementary school students.